The influence of workplace spirituality on nepotism and favoritism in Asean Regions - Khamis, Kamarul Azman; Kaliappen, Narentheren; Jermsittiparsert, Kittisak; Omar, Rusdi (Index Copernicus Ltd, 2020)
Many business ethics researchers have focused on new methods and theories of research which contribute substantially to improve business standards and ethics globally. The purpose of this research is to examine the influence of the workplace spirituality (WPS) with its four components, such as transcendence, meaningful at workplace, compassion and mindfulness on nepotism and favoritism (N&F) in the ASEAN region. Data were collected from services sector employees employed in Thailand, Indonesia and Malaysia through selfadministered questionnaires. The data analysis was performed using SPSS version 23.0 and Smart PLS 3.0. This research results indicate that WPS has a negative and significant influence on N&F. Furthermore, transcendence, meaningful at workplace, compassion and mindfulness have a negative and significant impact on N&F. The result of the current study also indicates that gender has no moderating influence on the relationship between mindfulness and N&F. The current study provides empirical data from Asian countries to help policy makers and practitioners in the N&F process to eradicate corruption